Prognostic Risk Factors for Severe Outcome in the Acute Phase of Neonatal Hypoxic-Ischemic Encephalopathy: A Prospective Cohort Study - Agnese Suppiej; Giovanna Vitaliti; Giacomo Talenti; Vittoria Cuteri; Daniele Trevisanuto; Silvia Fanaro; Elisa Cainelli (MDPI AG, 2021)
In the first days after birth, a major focus of research is to identify infants with hypoxic-ischemic encephalopathy at higher risk of death or severe neurological impairment, despite therapeutic hypothermia (TH). This is especially crucial to consider redirection of care, according to neonatal outcome severity. We aimed to seek associations between some neonatal routine parameters, usually recorded in Neonatal Intensive Care Units, and the development of severe outcomes. All consecutive patients prospectively recruited for TH for perinatal asphyxia, born between February 2009 and July 2016, were eligible for this study. Severe outcome was defined as death or major neurological sequelae at one year of age. Among all eligible neonates, the final analysis included 83 patients. Severe outcome was significantly associated with pH and base excess measured in the first hour of life, mode of delivery, Apgar score, Sarnat and Sarnat score, electroencephalogram-confirmed neonatal epileptic seizures, and antiepileptic therapy. Studying univariate analysis by raw relative risk (RR) and 95% confidence intervals (CI), severe outcome was significantly associated with pH (p = 0.011), Apgar score (p = 0.003), Sarnat score (p < 0.001), and Caesarian section (p = 0.015). Conclusions. In addition to clinical examination, we suggest a clinical-electroencephalographic protocol useful to identify neonates at high neurological risk, available before rewarming from TH.